Colorectal cancer and gut viruses: a visualized analysis based on CiteSpace knowledge graph - Jian, Chu; Jing, Zhuang; Yinhang, Wu; Jinlong, Duan; Yuefen, Pan; Quan, Qi; Shuwen, Han (Frontiers in Microbiology, 2023)
Background: Gut microbiome is a complex community of microbes present in the human gut and plays an important role in the occurrence and progression of colorectal cancer (CRC). However, the relationship between virus and CRC has not been fully understood. Objective: To explore the hot spots and research trends in the field of CRC and virus. Methods: By using the bibliometric analysis tool CiteSpace and based on the articles of the Web of Science Core Collection (WoSCC) database, the country, institution, highly cited literature, keywords and so on were visually analysed. Results: A total of 356 research articles on CRC from 2001 to 2023 were thoroughly analysed. The USA and China have made the largest contribution in the field of virus and CRC. The Helmholtz Association published the most papers. There were relatively few cooperations among institutions from different countries. The results of keyword cluster analysis proved that the literature on the relationship between human cytomegalovirus (CMV) and CRC was the most widely studied aspect in this field. "Gut microbiota", "inflammatory bowel disease", "hepatitis b virus", and "human papillomavirus infection" are the current research hotspots; "oncolytic virus", "apoptosis", and "gut microbiome" are the recent research frontiers and should be paid closer attention. Conclusions: By using CiteSpace bibliometric software, the visual analysis reflected the research trends and hot topics of virus and CRC. In addition, the prevalence and mechanism of specific virus on CRC were also reviewed, which provides valuable references for future CRC research.